Pertanggungjawaban Pidana atas Penyalahgunaan AI Generatif: Celah Hukum dalam KUHP Baru dan UU ITE - Mahmud; Nurfaidah (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
The rapid development of generative artificial intelligence (AI) technology has brought significant changes to various aspects of life, including the field of criminal law. On the one hand, this technology offers great benefits in terms of efficiency and innovation; on the other hand, it also opens the door to various new forms of crime, such as the creation of deepfake content, the spread of disinformation, and fraud based on digital impersonation. Problems arise when the existing legal framework, particularly in the new Criminal Code and the Law on Information and Electronic Transactions (ITE Law), does not explicitly regulate the misuse of generative AI. This creates a legal loophole in determining the form of criminal liability, especially regarding the element of fault (mens rea) and the legal subjects that can be held liable. This study aims to analyze the concept of criminal liability for the misuse of generative AI and to identify legal loopholes in the new Criminal Code and the UU ITE. The method used was normative legal research employing a legislative and conceptual approach, supported by primary and secondary legal sources. The findings indicate that while certain provisions in the new Criminal Code and the ITE Law can be used to prosecute perpetrators, there remain limitations in addressing the complexity of AI-based crimes, particularly regarding the burden of proof, attribution of acts, and the determination of liable parties. A reformulation of the law is needed that is more adaptive to technological developments, including specific regulations regarding generative AI as well as adjustments to the concept of criminal liability so as to provide legal certainty and effective protection for the public.